Investigation of Phosphate Removal from Aqueous Solutions Using Zinc Extraction Waste - Feride Naime Türk (Firat University Journal of Experimental and Computational Engineering)

(untitled)
It is important for waste management to economically evaluate the solid leach residues released in zinc production facilities and classified as hazardous waste due to the metals they contain, without harming the environment and human health. Although the disposal of these residues often requires special technologies, hazardous wastes are left to the environment or landfills due to the expense of these technologies and the inadequacy of legal sanctions in some cases. For this reason, it is important from an economic and environmental perspective to evaluate these residues and bring them into the industry. In this study, lead cake formed during zinc extraction production, brought from Kayseri Çinkur enterprises, was used. Since this waste contains high amounts of lead as well as zinc and iron, the conditions for removing phosphate from aqueous solutions were investigated. Phosphate removal adsorption isotherms were obtained using the obtained batch test results. Additionally, some thermodynamic quantities regarding phosphate removal were calculated. As a result of the experiment, it was determined that the P removal efficiency from aqueous solutions significantly depends on the solution pH and the dose of waste lead cake. It was also determined that phosphate removal from aqueous solutions obeyed the Langmuir and Freundlich isotherm. Additionally, it was observed that phosphate adsorption equilibrium was established after a period of 120 min. By mixing 100 mg/L phosphate solution with pH 7.69 with 20 g/L lead cake without any addition and contacting for 120 minutes, approximately 74% of the phosphate can be effectively removed by adsorption.